2020
DOI: 10.3390/nursrep10020012
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Questionnaire to Measure Knowledge of and Attitude toward COVID-19 among Nursing Students in Greece

Abstract: Background: During the COVID-19 pandemic, nursing students have had a key role in supporting the healthcare sector. They can join healthcare professionals in clinical practice or provide information to increase citizens’ levels of knowledge and their compliance with the restriction measures. The study aimed to develop and validate a tool to measure knowledge of and attitudes toward COVID-19 among nursing students in Greece. Methods: A questionnaire was developed through theoretical research and expert consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In general, mental health status of nursing students has deteriorated during the pandemic. Many studies have reported high level of depression and anxiety during the COVID-19 period ( Mechili et al, 2020 ; Patelarou et al, 2020 ). The measures undertaken by national governments (such as quarantine), the regular discussion in traditional and modern media have probably contributed in fear increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, mental health status of nursing students has deteriorated during the pandemic. Many studies have reported high level of depression and anxiety during the COVID-19 period ( Mechili et al, 2020 ; Patelarou et al, 2020 ). The measures undertaken by national governments (such as quarantine), the regular discussion in traditional and modern media have probably contributed in fear increase.…”
Section: Discussionmentioning
confidence: 99%
“…The second wave of COVID-19 pandemic is now hitting European countries with the total number of confirmed cases exceeding 87 million and 1.9 million deaths ( Looi, 2020 ). The impact of the pandemic is far more than a health crisis as it is affecting society and economy and although it varies from country to country it will definitely increase poverty, unemployment, social distancing, self- isolation, inequalities globally with serious psychosocial impact ( Nicola et al, 2020 ; Patelarou et al, 2020 ). As a result, responding swiftly to the pandemic and beat COVID-19 has now become the most important thing for humanity.…”
Section: Introductionmentioning
confidence: 99%
“…The second wave of COVID-19 pandemic is now hitting European countries with the total number of confirmed cases exceeding 87 million and 1.9 million deaths until now (January 2021) [2]. The impact of the pandemic is far more than a health crisis as it is affecting society and economy and although it varies from country to country it will definitely increase poverty, unemployment, social distancing, self-isolation, inequalities globally with serious psychosocial impact [3,4,5]. As a result, responding swiftly to the pandemic and beat COVID-19 has now become the most important thing for humanity.…”
mentioning
confidence: 99%
“…Until now, several questionnaires and scales have created to examine psychological impact of COVID-19 and mainly examine stress, anxiety or fear (Ahorsu et al, 2020; Arpaci et al, 2020; Feng et al, 2020; Lee, 2020; Lins and Aquino, 2020; Repišti et al, 2020; Taylor et al, 2020; Voitsidis et al, 2021). Also, several other questionnaires have developed to measure knowledge, attitudes, and practices about the COVID-19 (Bekele et al, 2020; Dardas et al, 2020; Patelarou et al, 2020; Saadatjoo et al, 2021; Srichan et al, 2020). To the best of our knowledge, no fully validated questionnaire to measure attitudes toward COVID-19 vaccination and pandemic exists.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire includes 16 items which were simple and understandable to the participants. For this reason, filling out the questionnaire is a straightforward process and requires only a short time (about 5 minutes).Several questionnaires have been developed to measure knowledge, attitudes, and practices about theCOVID-19 (Bekele et al, 2020;Dardas et al, 2020;Patelarou et al, 2020;Saadatjoo et al, 2021;Srichan et al, 2020). Each questionnaire has pros and cons.These questionnaires have been developed over the last 20 months and each one has attempted to capture attitudes during the period of the pandemic in which it developed.…”
mentioning
confidence: 99%